Efficacy and Tolerability of Erlotinib 100 mg/d vs. Gefitinib 250 mg/d in EGFR-Mutated Advanced Non-small Cell Lung Cancer (E100VG250): An Open-Label, Randomized, Phase 2 Study - Zhao, Shen; Zhang, Zhen; Fang, Wenfeng; Zhang, Yaxiong; Zhang, Zhonghan; Hong, Shaodong; Ma, Yuxiang; Zhou, Ting; Yang, Yunpeng; Huang, Yan; Zhao, Hongyun; Zhang, Li (Frontiers in Oncology, 2020)
Background: Erlotinib-based combination therapy leads to increased efficacy but also toxicity for EGFR-mutated NSCLC. Reducing the dose of erlotinib could improve treatment tolerability, but few evidences are available regarding its efficacy at reduced dose. This randomized phase-2 study intends to compare the efficacy and tolerability between lower dose erlotinib (100 mg/d) and standard dose gefitinib (250 mg/d) in EGFR-mutated NSCLC. Methods: Patients with EGFR-mutated advanced NSCLC were randomized at 1:1 ratio to receive erlotinib 100 mg/d or gefitinib 250 mg/d until disease progression or unacceptable toxicity. The primary endpoint was disease control rate (DCR). Results: Between April 2013 and September 2018, 171 patients were randomized to receive erlotinib (n = 85) and gefitinib (n = 86); 74 in the erlotinib group and 83 in the gefitinib group were include in analysis. DCR with erlotinib and gefitinib were 91% [95% CI 81.7–95.3] and 93% [85.1–96.6], respectively (P = 0.613). Response rate was 62% [50.8–72.4] in the erlotinib group and 53% [42.4–63.4] in the gefitinib group (P = 0.247). No significant difference was observed between erlotinib and gefitinib in median progression-free survival [10.1 vs. 11.3 months, HR = 1.295 [0.893–1.879], P = 0.171] and median overall survival [26.6 vs. 28.7 months, HR = 0.999 [0.637–1.569], P = 0.998]. Subgroup analyses by line of treatment, EGFR subtypes and status of central nervous system (CNS) metastasis found similar results. More toxicity [any-grade, 80 [96%] vs. 66 [89]; grade 3–4, 11 [13%] vs. 4 [5%]] and toxicity-related discontinuation [10 [12%] vs. 3 [4%]] occurred with gefitinib compared with erlotinib. But no significant difference was observed. Conclusion: Lower dose erlotinib (100 mg/d) achieved comparable efficacy compared with standard dose gefitinib (250 mg/d) in EGFR-mutated NSCLC. Clinical Trial Registration:https://clinicaltrials.gov, identifier: NCT01955421.